Performance analysis for adaptive channel estimation exploiting cyclic prefix in multicarrier modulation systems. - Xiaowen Wang (IEEE Transactions on communications)
Multicarrier modulation (MCM) has gained growing interest in high-data-rate communications in both wire and wireless environments. The channel estimation is a crucial aspect in MCM systems. In this paper, we first present a novel adaptive channel estimation algorithm exploiting the channel information contained in the cyclic prefix of the MCM system. In simulation, we show that this algorithm outperforms the existing scheme. Then we theoretically analyze the performance of the adaptive algorithm considering both channel noise and decision error. We prove that the algorithm is guaranteed to converge with proper loading. Computer simulation shows that our analytical results are quite close to the simulation.